Analisis Keterampilan Gerak Teknik Renang Gaya Dada - Geri Dicki Fernandaes; Maidarman Maidarman; Naluri Denay; Donie Donie (Jurnal Patriot, 2021)
Based on the observations, the problem in the study was an error that occurred in the breaststroke swimming technique movement of the Mountain Swimming Club Swimming Club in Padang City. Where this is thought to be the cause of the low performance of athletes at the club. This study aims to determine the breaststroke swimming technique skills. The research design is descriptive. Where the research sample is all athletes of Gunung Swimming Club Padang City, amounting to 9 people with saturated sampling technique. To measure swimming technique skills, it is carried out using an observation sheet and is assessed by 3 judgments (assessors) who have expertise in the sport of swimming. The results of the study: (1) The level of mastery of the breaststroke swimming technique of the Padang City Swimming Club athletes is currently at a moderate level. Where the results of data analysis obtained a maximum score of 68 (very good), a minimum score of 40 (less), a standard deviation of 8 and an average score of 56 (moderate). (2) Out of 9 people: 1 person (11.1%) has very good mastery of the breaststroke swimming technique. 3 people (33.3%) have mastery of the breaststroke swimming technique in the good category. 4 people (44.5%) had mastery of the breaststroke technique in the moderate category. 1 person (11.1%) has mastery of the breaststroke swimming technique in the very poor category. Conclusion Currently, the level of mastery of the breaststroke swimming technique of the Padang City Swimming Club athletes is at a moderate level.